Evaluation of interleukin-9 expression as a potential therapeutic target in chronic lymphocytic leukemia in a cohort of Egyptian patients - Abbassy, Hadeer A.; Aboelwafa, Reham A.; Ghallab, Omar M. (International Journal of Research in Medical Sciences, 2017)
Background: Chronic lymphocytic leukemia (CLL) is a common lymphoid malignancy that has a highly variable clinical course. Genomic features as zeta-chain-associated protein kinase 70 (ZAP70) expression and CD38 expression provide further differentiation of disease prognosis. Extensive studies have confirmed the oncogenic activities of IL-9 in lymphoma. The aim of the current study was to investigate the contribution of IL-9 expression to the pathogenesis of CLL and its correlation to other prognostic parameters. Methods: This study was conducted on 80 patients at diagnosis with CLL and 80 healthy controls. Using real time polymerase chain reaction and enzyme linked immunosorbant assay, IL-9 mRNA expression and its serum level were compared between patients and controls. They were both correlated with other prognostic factors. Results: There was an overexpression of IL-9 in CLL patients that correlated with modified Rai staging, ZAP70, CD38 and all hallmarks of an active and aggressive disease. The correlation between IL-9 upregulation and patient characteristics provided a direct clinical evidence for its contribution to the pathogenesis of CLL. Conclusions: Significantly higher expression of IL -9 measured at both the mRNA and the protein levels in patients with CLL that correlates with more complex course of the disease and worse prognosis may allow one to speculate its importance in the pathogenesis of the disease and its possible role as a potential therapeutic target.